ANALISIS FRAMING PEMBERITAAN KASUS PEMBUNUHAN IBU MUDA DI BEKASI PADA MEDIA ONLINE KOMPAS.COM - Dinny Indhikri Az'zahra; Rajendra Walad Jihad (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2024)
Murder cases are cases that often covered by media. The murder case of young mother that occurred in West Cikarang, Bekasi Regency, West Java Province in early September 2023 was also widely covered by various media, including Kompas.com. Before it published, the reality murder case of young mother in Bekasi had been constructed first by media. The construction is carried by highlighting or omitting certain information according to media's interest. Therefore, this study aims to find how the construction of news murder case of young mother in Bekasi at online media Kompas.com the period of September 13-15, 2023. The method used in this study is qualitative method with the Robert N. Entman framing analysis approach. The results this study show that Kompas.com construct the murder incident that befell young mother in Bekasi as fault of police who were ignorant or not serious in handling the victim's domestic violence report. Kompas.com raised the issue the role of police in handling reports of domestic violence victims before the murder by highlighting aspects that tend to lead negative frames. The three news stories analyzed in this study have same frame, namely demanding the police to more serious in handling domestic violence reports.